ABUJA RESIDENTS’ PERCEPTION OF MASS MEDIA COVERAGE OF THE 2023 PRESIDENTIAL ELECTION CAMPAIGN IN NIGERIA - DANIEL T. EZEGWU; AGNES. O. EZEJI; GLORIA NWAKEGO CHUKWUEMEKA; CHIOMA ROSE CHIME-NGANYA (International Studies Journal)
This study assessed Abuja residents’ perception of mass media coverage of the 2023 Presidential election campaign in Nigeria. Previous studies have either looked at print media, broadcast media or social media coverage of elections in Nigeria. This study examined mass media coverage of Nigeria's 2023 presidential election campaign. Elections in Nigeria, especially presidential usually polarize Nigerians along the ethnic background. This contributes to existing literature by examining the issue. The objectives of the study were to: Determine the extent to which Abuja residents were exposed to mass media coverage of the 2023 presidential election campaign in Nigeria, find out the mass media channels through which Abuja residents were exposed to the 2023 presidential election campaign, and find out Abuja residents’ perception of mass media coverage of 2023 Presidential election campaign. The researcher used a survey research method. The researcher found that the majority of Abuja residents were highly exposed to mass media coverage of the 2023 presidential election campaign in Nigeria. Further findings revealed that Abuja residents were exposed to the mass media coverage of the 2023 presidential election campaign through the radio medium.  Also, 38% of the respondents perceived mass media as less effective in the coverage of the 2023 presidential election. The study concludes that most Abuja residents were highly exposed to mass media coverage of the 2023 presidential election campaign in Nigeria and they accessed the coverage through radio medium. The researchers recommended that subsequently, political parties in Nigeria should use the radio medium to pass their campaign messages than other forms of media since most respondents accessed the 2023 presidential election campaign through the medium.